PENGEMBANGAN PERANGKAT PEBELAJARAN MATEMATIKA DENGAN MODEL CONCEPT ATTAINMENT BERBANTUAN CD INTERKATIF PADA MATERI SEGITIGA KELAS VII - Winasmadi, Praja Achsani (JPP, 2011)
This study aimed to provide mathematics learning devices with concept attainment modelassisted by interactive CD on the triangle material of the 7th grade students that arevalid, practical, and effective. The development of mathematics learning devices is doneby referring to the model of Plomp educational development. The learning devices experimentwas held in the VII F class of SMP N 1 Pringsurat. Methods of data collectionthrough testing, documentation, observation, and questionnaires. The results of assessmentdata analysis from the experts validation obtained the mathematics learning deviceswith concept attainment model assisted by interactive CD that are valid, it was obtainedthat the learning devices are qualified for the practicality criteria they are the students responseand the results of the learning management are good or well and it is also qualifiedfor the effectiveness criteria: (1) learning is chefment minimum criteria; (2) themean of the experimental class was better than the control class; and (3) the students’ activityand motivation influenced the test of the students’ learning results about 49,1%.For this reason, it can be concluded that the development of learning devices with theconcept attainment assisted by interactive CD on the triangle material of the 7th gradestudents are valid, practical, and effective.Keywords: Development Learning Devices, Concept Attainment Model, Interctive CD